Sex-Related Differences in the Immune Response to Meningococcal Vaccinations During Adolescence - Ohm, Milou; Boef, Anna G. C.; Stoof, Susanne P.; van Ravenhorst, Mariëtte B.; van der Klis, Fiona R. M.; Berbers, Guy A. M.; Knol, Mirjam J. (Frontiers in Public Health, 2022)
Background Immune responses to pediatric vaccinations have been reported to differ according to sex. Such sex-differential responses may become more pronounced during adolescence due to hormonal differences. We investigated whether the vaccine response following primary vaccination against meningococcal serogroup A (MenA), MenW and MenY and booster vaccination against MenC differed between girls and boys using data from two clinical studies. Methods Children aged 10, 12 and 15 years, who had been primed with MenC vaccination between 14 months and 6 years of age, received a booster MenC vaccination or MenACWY vaccination. Polysaccharide-specific IgG concentrations and functional antibody titers (determined with the serum bactericidal antibody [SBA] assay) were measured at baseline, 1 month, 1 year, and 3 years (only MenC group) after vaccination. We calculated geometric mean concentrations and titers (GMC and GMT) ratios for girls versus boys adjusted for age group. Additionally, we compared the proportion protected individuals between girls and boys at all timepoints. Results This study included 342 girls and 327 boys from two clinical trials. While MenAWY antibody levels did not differ consistently one month after vaccination, all GMC- and GMT-ratios were in favour of girls one year after vaccination (range: 1.31 [1.02-1.70] for MenA IgG to 1.54 [1.10-2.16] for MenW IgG). Overall, MenC antibody levels were slightly higher in girls at all postvaccination timepoints (GMC- and GMT-ratios: 1.16/1.17 at one month, 1.16/1.22 at one year and 1.12/1.15 three years postvaccination). Higher MenC antibody levels were observed in 12- and 15-year-old girls compared to boys of the same age, whereas 10-year-old boys and girls had similar antibody levels. The percentage of participants protected (SBA titer ≥8) was very high (95-100%) at all timepoints, and did not differ significantly between boys and girls. Conclusion Antibody responses were higher in girls than in boys for all serogroups at most timepoints after primary MenAWY vaccination and booster MenC vaccination. The differences in average titers were however small and the percentage participants with protective titers was very high for both sexes.